A RADIOGRAPHY OF HIGHER EDUCATION IN ROMANIA AFTER 1989 - NELA ȘTELIAC (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2020)
The present paper brings to attention the evolution of higher education in Romania after 1989, carrying out in this sense a quantitative analysis through the prism of specific indicators. The Romanian higher education has undergone great transformations in the last 30 years. Two major periods were identified in its evolution: the first being the expansion and the second, contraction. In the first stage, the number of universities, the number of faculties, the number of enrolled students, the number of graduates increased exponentially. Also, although not at the same pace as the number of students, the number of teachers serving universities has also increased. Starting with 2005, the Bologna system was adopted, which involved switching to the three cycles. Gradually, evening education disappeared. There have been changes in the structure of specializations by reducing the share of students enrolled in technical specializations in favor of those from economic, law science and university-pedagogical specializations. In the second stage there was a certain contraction of higher education, determined by the reduction of the birth rate, the emigration of the population after 1990, the emigration of high school graduates to study abroad, the reduction of the quality of higher education. Most of the school population in tertiary education is made up of undergraduate students. In terms of forms of education, the largest share is held by students in full-time learning education.